Implementasi Game Edukasi Adaptif untuk Anak Berkebutuhan Khusus di Yayasan Yenaiz Kota Tangerang - Ariessanti, Hani Dewi; Asri, Jefry Sunupurwa; Laksana, Ryan Putra; Suharti, Dwi Sloria; Fikri, Muhammad; Dzaki, Muhammad Thifaal; Erlangga, Ravi Era; Fathir, Mohammad Nafilah; Putraku, Daniel Marciano; Raditya, Paramadinah Aqil (Abdimas Universal, 2026)
This community service activity aims to improve the quality of learning and the well-being of children with special needs through the use of mobile-based technology. The partner institution faces several challenges, including limited adaptive learning media, the continued use of conventional teaching methods, and a shortage of caregivers for optimal assistance, resulting in less structured learning processes and limited support for children's independence. To address these issues, an adaptive educational game was implemented as a mobile application designed with simple visuals, interactive features, and offline usability to suit the children's needs. The implementation method included program socialization, training for caregivers on how to use the application, direct application in daily activities, and evaluation through observation and discussion. The results show that the use of the educational game increases children's engagement in learning activities, helps them understand daily routines more effectively, and supports caregivers in providing more efficient assistance. Therefore, the adaptive educational game can serve as an effective, user-friendly, and sustainable learning medium for children with special needs.